Application of controlled-release compound fertilizer to mechanically dry direct-seeded rice increased rice biomass, nutrient accumulation and yield. (10th November 2022) - Yuan, Manman; Sun, Yixiang; Wang, Jiabao; Wu, Gang; Hu, Peng; Zhang, Xiangming; Wang, Wenjun; Jing, Yudan
Abstract: To clarify the effects of mechanically dry direct-seeded rice (MD-DSR) through drilling and controlled-release compound fertilizer (CRF) on rice production, field experiments were carried out with mixed controlled-release urea; controlled-release potassium; and common urea, phosphorus and potash fertilizers as test materials. The experiment was implemented with a split-plot design, with fertilization modes as the main plots and two varieties ( indica and japonica ) as the subplots. The fertilization modes were a one-time application of CRF (denoted Indica and Japonica when applied to indica and japonica, respectively), a basal application of CRF followed by topdressing with urea at the tillering stage (Indica + N, Japonica + N) and three-time fertilization, representing typical farmer fertilization practices (FFP) (Indica + FFP, Japonica + FFP). The results showed that the yields of indica and japonica rice were 5.5–15.8% and 5.3–16.3% higher, respectively, under the two CRF treatments than under FFP in the 3 years of the experiment. The effective tiller percentage, shoot and root biomass, root-shoot ratio, and harvest index of the population and the biomass per plant of indica and japonica rice improved under the two CRF treatments relative to FFP. The Indica + FFP and Japonica + FFP plants exhibited higher total N accumulation but significantly lower fertilizer partial productivity than the corresponding plants under the two CRF treatments. The net benefits to indica and japonica under the two CRF treatments were higher than those under FFP. Therefore, MD-DSR combined with the one-time application of CRF can increase rice yield, reduce fertilizer and labor costs, and benefit rice production.